Using storytelling to unpack resilience theory in accordance with an internationally recognised resilience framework with primary school children. Issue 1 (12th June 2022) - Tillott, Sarah; Weatherby-Fell, Noelene; Pearson, Phil; Neumann, Michelle M.
Abstract: Resilience can be a protective trait to promote mental health when implemented in the early years. This study explored the use of storytelling to foster children's learning of resilience. A pedagogically appropriate storybook was used to facilitate and embed the skills of resilience in children at primary school. Teachers ( n = 2) and community-based sports officers ( n = 2) read the storybook to children enrolled in Kindergarten (first formal year of schooling) ( n = 20), Year 1 ( n = 20) and Year 2 ( n = 20). The total number in the participant group was 60, aged 4–8 years old. Following the initial reading, teachers continued to deliver the storybook to children over a 4-week intervention period. All participants were interviewed about their perceptions of the storybook, and their responses were coded into key themes mapped by the Grotberg Resilience Framework. Results indicated that storytelling as a tool provided children with positive resilience-based behavioural intervention opportunities.